Multispecies pasture diet and cow breed affect the functional lipid profile of milk across lactation in a spring-calving dairy system - Renata Kostovska; Gaetan Drouin; Joaquín J. Salas; Mónica Venegas-Calerón; Brendan Horan; John T. Tobin; Tom F. O'Callaghan; Sean A. Hogan; Alan L. Kelly; Laura G. Gómez-Mascaraque (Journal of Dairy Science)
ABSTRACT: This study compared the effect of 2 pasture-based feeding systems, namely a traditional perennial ryegrass (PRG) diet, and a recently introduced, more sustainable multispecies swards (MSS) diet, on the functional lipid profile of raw milk. In addition to the 2 pasture diets, the study uniquely examined the combined effects of breed, namely Holstein Friesian (HF) or Jersey Holstein Friesian (JFX), and lactation stage in Ireland, spanning from March to November. Bulk milk samples (n = 144 yearly) for the 4 groups examined were collected for 4 wk per each of the 9 mo specified. Changes in total fatty acid (FA) and triglyceride carbon number profiles were determined by GC with a flame ionization detector, and those in polar lipids (PL) content by HPLC–evaporative light scattering–MS. Based on multivariate analysis, both diet (34.0% contribution) and breed (19.1% contribution) influenced milk FA on a yearly basis; however, in early lactation there were no differences in FA profile between the groups. In middle lactation and late lactation (LL), the MSS diet increased proportions of nutritionally beneficial n-6 and n-3 PUFA in milk, including C18:3 n-3 (ALA), C18:2 n-6 (LA) and C22:5 n-3 (DPA). Although proportions of ALA and LA increased in MSS milks, the LA/ALA ratio remained around 1 for the 2 feeding systems, confirming the beneficial modulation of LA and ALA in milks from pasture-based diets. Particularly in LL, the milk of JFX cows tended to have increased de novo FA, compared with HF, suggesting implications for techno-functional properties of dairy products such as butter. The milk of PRG HF group showed improved health-promoting properties, with lower thrombogenicity and atherogenicity indices on a yearly basis. Regarding techno-functional properties, the PRG HF group resulted in higher oleic acid reflecting in lower spreadability index, suggesting that butter made of this group would be more spreadable, compared with the one made from the other milk groups examined. The triglyceride and PL profiles were mainly affected by stage of lactation. Overall, these results show the effects of cow diet, breed, and stage of lactation on milk lipid profile, with important implications for the nutritional and techno-functional characteristics of dairy products.